1982
DOI: 10.1002/nav.3800290114
|View full text |Cite
|
Sign up to set email alerts
|

Scheduling of a single machine to minimize total weighted completion time subject to release dates

Abstract: In this paper the n/I/q 2 O / x wjCj problem under the assumptions of nonpreemptive sequencing and sequence independent processing times is investigated. After pointing out the fundamental properties, some dominance sufficient conditions among sequences are obtained and a branch and bound algorithm is proposed. Computational results are reported and discussed.i

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
1
1

Year Published

1990
1990
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(40 citation statements)
references
References 9 publications
0
38
1
1
Order By: Relevance
“…The descriptive work of Kanet (1981) has shown that the set of active schedules, although dominant over the set of nondelay schedules, is signiÿcantly larger. This is where contributions like those of Bianco and Ricciardelli (1992), Carlier (1982), Erschler et al (1983) and Chu and Portmann (1992) play a role. In each case the results serve to reduce the required search space within active schedules for a speciÿc scheduling objective.…”
Section: A Taxonomy For Iit Scheduling Problemsmentioning
confidence: 99%
See 1 more Smart Citation
“…The descriptive work of Kanet (1981) has shown that the set of active schedules, although dominant over the set of nondelay schedules, is signiÿcantly larger. This is where contributions like those of Bianco and Ricciardelli (1992), Carlier (1982), Erschler et al (1983) and Chu and Portmann (1992) play a role. In each case the results serve to reduce the required search space within active schedules for a speciÿc scheduling objective.…”
Section: A Taxonomy For Iit Scheduling Problemsmentioning
confidence: 99%
“…For example, it may be possible to exploit the results of Bianco and Ricciardelli (1992) when addressing the 1|d j | j E j problem. Such an Venn diagram illustrating the relation of timetabled schedules to active and nondelay schedules.…”
Section: Research Opportunitiesmentioning
confidence: 99%
“…Lenstra et al [16]. Note, that Bianco and Ricciardelli [4] propose an exact algorithm for (1/ rj/ C M ).…”
Section: Phase I-batching: the Single Machine Casementioning
confidence: 99%
“…Since the total completion time minimization is equivalent to total (mean) flow time, total (mean) waiting time and total (mean) lateness minimization (Conway, Maxwell and Miller, 1967), these latter criteria are over-regular as well. This problem has been extensively studied in single machine case with unequal release dates (Ahmadi and Bagchi, 1990;Liu and MacCarthy, 1991;Belouadah, Posner and Potts, 1992;Bianco and Ricciardelli, 1982;Chandra, 1979;Deogun, 1983;Dessouky and Deogun, 1981;Hariri and Potts, 1983). Among the optimal algorithms, the one proposed by Chu (1992è) capable of solving problems with up to 100 jobs seems to be the most effective.…”
Section: {0mentioning
confidence: 99%